The effect of the inflammatory reflex on the heart - Kamenov, Aleksandar; Stojiljković, Vladimir; Živić, Saša; Lazarević, Milan; Golubović, Mlađan; Milić, Dragan; Gmijović, Marko (Acta medicae Medianae, 2020)
The native immune system is the main component of defense against pathogen, injury and trauma. Vagal fibers contain sensory and motor components controlling different functions such as heart frequency and digestion. There are lots of reasons this nervous based anti-inflammatory pathway is useful, the cholinergic anti-inflammatory pathway, which is fast, separate and localized in tissue where the injury originated and can induce humoral systemic anti-inflammatory response which has a number of usefull effects on a number of heart diseases.